Topoisomerase 3? is the major topoisomerase for mRNAs and linked to neurodevelopment and mental dysfunction. - Ahmad, M.; Shen, W.; Li, W.; Xue, Y.; Zou, S.; Xu, D.; Wang, W. (Nucleic Acids Research, 2017)
Human cells contain five topoisomerases in the nucleus and cytoplasm, but which one is the major topoisomerase for mRNAs is unclear. To date, Top3? is the only known topoisomerase that possesses RNA topoisomerase activity, binds mRNA translation machinery and interacts with an RNA-binding protein, FMRP, to promote synapse formation; and Top3? gene deletion has been linked to schizophrenia. Here, we show that Top3? is also the most abundant mRNA-binding topoisomerase in cells. Top3?, but not other topoisomerases, contains a distinctive RNA-binding domain; and deletion of this domain diminishes the amount of Top3? that associates with mRNAs, indicating that Top3? is specifically targeted to mRNAs by its RNA binding domain. Moreover, Top3? mutants lacking either its RNA-binding domain or catalytic residue fail to promote synapse formation, suggesting that Top3? requires both its mRNA-binding and catalytic activity to facilitate neurodevelopment. Notably, Top3? proteins bearing point mutations from schizophrenia and autism individuals are defective in association with FMRP; whereas one of the mutants is also deficient in binding mRNAs, catalyzing RNA topoisomerase reaction, and promoting synapse formation. Our data suggest that Top3? is the major topoisomerase for mRNAs, and requires both RNA binding and catalytic activity to promote neurodevelopment and prevent mental dysfunction.